Spatiotemporal dynamics of information encoding revealed in orbitofrontal high-gamma. Issue 1 (December 2017) - Rich, Erin; Wallis, Joni
Abstract High-gamma signals mirror the tuning and temporal profiles of neurons near a recording electrode in sensory and motor areas. These frequencies appear to aggregate local neuronal activity, but it is unclear how this relationship affects information encoding in high-gamma activity (HGA) in cortical areas where neurons are heterogeneous in selectivity and temporal responses, and are not functionally clustered. Here we report that populations of neurons and HGA recorded from the orbitofrontal cortex (OFC) encode similar information, although there is little correspondence between signals recorded by the same electrode. HGA appears to aggregate heterogeneous neuron activity, such that the spiking of a single cell corresponds to only small increases in HGA. Interestingly, large-scale spatiotemporal dynamics are revealed in HGA, but less apparent in the population of single neurons. Overall, HGA is closely related to neuron activity in OFC, and provides a unique means of studying large-scale spatiotemporal dynamics of information processing. High gamma activity (HGA) and local neurons encode similar information, but it's unclear if this is true when neurons are heterogeneous, as in the orbitofrontal cortex (OFC). Here, Rich & Wallis show that HGA in OFC is closely related to neuron firing, but reveals clearer spatiotemporal dynamics.